Analysis of Employee Services through a Community Approach in Increasing Customer Interests in Saving at BPRS Bhakti Sumekar - Jannah, Khozinatul; Romlah, Romlah; Sholihah, Imroatus (Sahwahita: Community Engagement Journal, 2024)
BPRS Bhakti Sumekar KC Madya Pamekasan  is  a sharia financial institution which is surrounded by many  large  banks. The existence of these banks is a big challenge for BPRS Bhakti Sumekar KC Madya Pamekasan  to survive and be able to compete. This  research analyzes the relationship between employe service and  customers’  interest in saving at BPRS Bhakti Sumekar KC Madya Pamekasan. Data was obtained through structured interviews with branch heads and marketing managers. To ensure the level of trust in the information, data triangulation was carried out using different techniques, namely observation of the environment and forms of community services implemented at BPRS Bhakti Sumekar. All data analyzed to describe the impact of employee services oninterest in saving at BPRS Bhakti Sumekar KC Madya Pamekasan.  The research method involves  in-depth interviews with employees and customers, as well as direct observatiton of service interactions. The findings show that employee service quality plays  an important role in shaping customeers’  interes  in saving, with  interpersonal aspects and trust being the main factors. The implecations of this research can help BPRS Bhakti Sumekar in designing service strategies  that are more effective and focus on customer needs  and preferences The findings of this research show that customers' interest in saving is increasing due to adequate bonuses and community services that customers receive. Community services are provided in the form of football pick-up and drop-off services, balance printing services, and problem solving.